INFECTION PECULIARITIES OF PLACENTA IN WOMEN WITH PREMATURE RUPTURE OF MEMBRANES AT 22 - 36 WEEKS DEPEND ON LATENCY - Наталья Николаевна Елизарова; Наталья Владимировна Артымук; Марина Валерьевна Туриёва; Наталья Борисовна Колесникова; Дина Владимировна Павловская; Елена Валентиновна Гришкевич (The Publishing House Medicine and Enlightenment, 2017)
The purpose of this study was to study the morphological and microbiological features of the placenta in women with preterm premature rupture of membranes (PPROM) at 22+0-36+6 weeks, depending on the duration of the latency period. Material and methods. A retrospective, comparative, analytical study was conducted. The study included 188 patients, depending on the duration of the latency period, the following groups were identified: Group I - latency period up to 2 days; II group - latency period from 2 to 7 days; III group - latency period more than 7 days. Results. With the increase in latency period, the incidence of infection of the placenta increased, including, placental chorioamnionitis, subchorial intervillusitis, membranitis, vascular-stromal funikulitis in comparison with women with less duration of latency period. When the latency period more than 7 days were statistically significantly more often recorded hyperplastic form and subcompensation degree of placental insufficiency (PI) relative to women with less duration of latency period. The results of the microbiological study of the sequences did not depend on the duration of the latency period, but according to microbiological study, gram-positive flora is most often allocated: Staphylococcus epidermidis and Enterococcus faecalis.